2022
DOI: 10.7554/elife.74086
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that uniformly white sclera enhances the visibility of eye-gaze direction in humans and chimpanzees

Abstract: Hallmark social activities of humans, such as cooperation and cultural learning, involve eye-gaze signaling through joint attentional interaction and ostensive communication. The gaze-signaling and related cooperative-eye hypotheses posit that humans evolved unique external eye morphologies, including uniformly white sclera (the whites of the eye), to enhance the visibility of eye-gaze for conspecifics. However, experimental evidence is still lacking. This study tested the ability of human and chimpanzee parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Our results do not support an adaptive advantage for primates, as a taxon, to hamper the transmission of social gaze information between conspecifics in agonistic interactions, in line with the observation that nonhuman primates appear to readily detect gaze 49 . Furthermore, recent models 50 as well as experimental evidence 51 support the proposal that hyperpigmented conjunctiva (like those of chimpanzees) may contribute to a salient eye direction if the iris is bright 5 , owing to the contrast between adjacent tissues. Anthropoid primates are highly visual animals 52 that rely on attention structure (e.g., who looks at whom 53 ) to infer hierarchy.…”
Section: Discussionmentioning
confidence: 70%
“…Our results do not support an adaptive advantage for primates, as a taxon, to hamper the transmission of social gaze information between conspecifics in agonistic interactions, in line with the observation that nonhuman primates appear to readily detect gaze 49 . Furthermore, recent models 50 as well as experimental evidence 51 support the proposal that hyperpigmented conjunctiva (like those of chimpanzees) may contribute to a salient eye direction if the iris is bright 5 , owing to the contrast between adjacent tissues. Anthropoid primates are highly visual animals 52 that rely on attention structure (e.g., who looks at whom 53 ) to infer hierarchy.…”
Section: Discussionmentioning
confidence: 70%
“…Recently, an investigation using iridoscleral ratios found humans, bonobos and chimpanzees to have comparable, not distinct, gaze conspicuousness www.nature.com/scientificreports/ despite large differences in scleral pigmentation 5 . This methodology, however, does not account for physical properties of visible light that may bias the naturalistic perception of shade 6,7,10 , a phenomenon that has recently been shown to influence the successful recognition of an averted gaze, even between primate species 7 . Furthermore, another recent study suggested that variation in primate external eye morphology may be due to genetic drift 6 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with all three hypotheses of scleral evolution, suggesting that primate scleral morphologies evolve in relation to variation in social environment.The primate order contains a remarkable amount of variation in external ocular morphology (Fig. 1), including differences in scleral volume, width-height ratios and pigment profiles [1][2][3][4][5][6][7][8] . Scleral volumes and width-height ratios have been linked in phylogenetic comparative analyses to social (i.e., group size and neocortex ratio), ecological (i.e., habitat use) and life history (i.e., body mass) drivers 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the involvement of irido-scleral contrast in triadic communication 4 may not have been the most basal driver of selection for scleral depigmentation as proposed by Tomasello et al 3 , but the result of co-option. As we have no way of reaching into the past to interview our extinct ancestors, answers to such questions can only be approximated through comparative research with other animals, in particular other primates 11,14,43,47,[69][70][71] . The recent spike in such studies highlights the importance of comparative research in assessing the adaptive significance of human ocular morphology.…”
Section: Discussionmentioning
confidence: 99%